Hubungan Asupan Kafein terhadap Gangguan Tidur dan Status Gizi pada Mahasiswa Tingkat Akhir Program Sarjana Universitas Dr. Soekardjo - Siti Kayla Rulina Sausan; Dea Amanda Caressa; Agus Putra Murdani (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Increased caffeine intake is commonly used by students to cope with academic demands, especially during examinations and the completion of final projects. Excessive caffeine consumption may affected sleep quality and potentially influence nutritional status. This study aimed to determine the correlation between caffeine intake, sleep disturbances, and nutritional status among final – year unsergarduated students at Dr. Soekardjo University. This study used quantitative approach with an observational analytic and cross-sectinal design. A total of 108 students participated in the study. Data were collected using questionnaires and analyzed using the Spearman Rank correlations test. The findings indicated that the most of respondents with low caffeine intake experienced mild sleep disturbances, totaling 56 respondents (80%). Meanwhile, respondents with moderate and high caffeine intake mostly experienced moderated sleep disturbances, with 13 respondents (61.9%) and 9 respondents (52.9%), respectively. The results showed a significant correlation between caffeine intake and sleep disturbances (p-value=0.000). In all categories of caffeine intake, most respondents had normal nutritional status. However, no significant relationship was found between caffeine intake and nutritional status (p-value=0.351). In conclusion, caffeine intake was associated with sleep disturbances but not with nutritional status among final-year undergraduate students.